Formation and disruption of tonotopy in a large-scale model of the auditory cortex - Tomková, Markéta; Tomek, Jakub; Novák, Ondřej; Zelenka, Ondřej; Syka, Josef; Brom, Cyril (Journal of computational neuroscience, 2015)
There is ample experimental evidence describing changes of tonotopic organisation in the auditory cortex due to environmental factors. In order to uncover the underlying mechanisms, we designed a large-scale computational model of the auditory cortex. The model has up to 100 000 Izhikevich's spiking neurons of 17 different types, almost 21 million synapses, which are evolved according to Spike-Timing-Dependent Plasticity (STDP) and have an architecture akin to existing observations. Validation of the model revealed alternating synchronised/desynchronised states and different modes of oscillatory activity. We provide insight into these phenomena via analysing the activity of neuronal subtypes and testing different causal interventions into the simulation. Our model is able to produce experimental predictions on a cell type basis. To study the influence of environmental factors on the tonotopy, different types of auditory stimulations during the evolution of the network were modelled and compared. We found that strong white noise resulted in completely disrupted tonotopy, which is consistent with in vivo experimental observations. Stimulation with pure tones or spontaneous activity led to a similar degree of tonotopy as in the initial state of the network. Interestingly, weak white noise led to a substantial increase in tonotopy. As the STDP was the only mechanism of plasticity in our model, our results suggest that STDP is a sufficient condition for the emergence and disruption of tonotopy under various types of stimuli. The presented large-scale model of the auditory cortex and the core simulator, SUSNOIMAC, have been made publicly available.
Keywords: Models, Neurological; Nerve Net; sluchové korové centrum; modely neurologické; Oscillation; Computer Simulation; neurony; akustická stimulace; Animals; akční potenciály; lidé; Action Potentials; Auditory Cortex; Large-scale model; Humans; STDP; zvířata; nervová síť; Neurons; Acoustic Stimulation; počítačová simulace; Spiking neuron; Auditory cortex; Tonotopy